Decision Support System for Selection of The Best Doctor at Ahmad Brahim Hospital Using the Simple Additive Weighting (SAW) Method - Fahra, Reni; Rahim, Abdul; Latipah, Asslia Johar (JSE Journal of Science and Engineering, 2024)
The selection of the best doctors at the Ahmad Brahim hospital was not only done once, but the selection of the best health workers at the Ahmad Brahim hospital was also carried out, but the selection of the best health workers was still done manually by the health department. Therefore, to help speed up the research process, a website-based decision support system was created to select the best doctors to provide rewards with several methods that can be used. One of the methods used in making decisions is simple additive weighting (SAW) which is done by weighting each of the criteria used. Decision support website created using the PHP and MYSQL programming languages for data storage. This study has criterion 3, namely absence, attitude and diligence then have 7 alternatives, the 7 alternatives have 4 ratings 1 where the average assessment is the same as the absence score 0.45, the attitude value is 0.35 and the diligence value is 0.12 with a total value of 1 so those who get the first rank score are dr. Audi Pirade, dr. Kesatria Putra Abadi, dr. Nurfitri Rahmani Awaliyah and dr. Riska Ruswanti. Then the second rank is dr. Christi Angelia Arung Labi with an absence score of 0.45, an attitude value of 0.35 and a diligence value of 0.12 with a total of 0.92